2015
DOI: 10.1039/c5mt00053j
|View full text |Cite
|
Sign up to set email alerts
|

EPR spectroscopy identifies Met and Lys residues that are essential for the interaction between the CusB N-terminal domain and metallochaperone CusF

Abstract: Copper plays a key role in all living organisms by serving as a cofactor for a large variety of proteins and enzymes involved in electron transfer, oxidase and oxygenase activities, and the detoxification of oxygen radicals. Due to its toxicity, a conserved homeostasis mechanism is required. In E. coli, the CusCFBA efflux system is a copper-regulating system and is responsible for transferring Cu(I) and Ag(I) out of the periplasm domain into the extracellular domain. Two of the components of this efflux system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 48 publications
2
10
0
Order By: Relevance
“…While this suggests that the mechanism of transfer from CusF is similar between N-terminal truncate and full-length CusB, we cannot exclude the possibility that elements of the transfer process may differ in the full-length CusB−CusF complex. For example, recent studies have shown that the full-length CusB is a dimer in solution, and undergoes a conformational change to a more compact state on Cu(I) binding 46 , 47 . As a consequence, metal-induced changes in the overall protein scaffold may complicate the simple reversible transfer behavior observed between CusF and CusB-NT, or even render it irreversible, as recently suggested by Meir and coworkers 46 as a means of ensuring unidirectional Cu(I) efflux through the CusCBA complex.…”
Section: Discussionmentioning
confidence: 99%
“…While this suggests that the mechanism of transfer from CusF is similar between N-terminal truncate and full-length CusB, we cannot exclude the possibility that elements of the transfer process may differ in the full-length CusB−CusF complex. For example, recent studies have shown that the full-length CusB is a dimer in solution, and undergoes a conformational change to a more compact state on Cu(I) binding 46 , 47 . As a consequence, metal-induced changes in the overall protein scaffold may complicate the simple reversible transfer behavior observed between CusF and CusB-NT, or even render it irreversible, as recently suggested by Meir and coworkers 46 as a means of ensuring unidirectional Cu(I) efflux through the CusCBA complex.…”
Section: Discussionmentioning
confidence: 99%
“…The present study aimed to elucidate the various Cu(I) binding sites in CusB; we hypothesized that deletion of single methionine (Met) residues in CusB, which possibly play a role either in Cu(I) coordination [18, 2527], in the Cus channel assembly process, or in the transfer mechanism may also affect cell viability upon Cu(I) stress. Ten Met residues exist in CusB; in order to determine which of them are essential for cell growth, we introduced a single point mutation in one of them.…”
Section: Resultsmentioning
confidence: 99%
“…The trigger for opening the channel was shown to be the interaction between the metallochaperone CusF and the N-terminal domain of CusB (CusB_NT) associated with Cu(I) binding [2527, 46]. Previously we and others studied CusB_NT and elucidated the significance of the three conserved methionine residues (M49, M64, and M66) for Cu(I) binding within CusB_NT [21, 23, 26, 27]. Crystallography suggested two additional Cu(I) binding sites in domain 1 and domain 4 [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the crystal structure suggests that there are two methionine residues ((i) M190, domain 4, and (ii) M324, domain 1), which are not conserved, yet take part in Cu(I) binding [18]. The most studied region in CusB is the N-terminal domain (CusB_NT), which comprises 60 amino acids (residues 28–88) that were shown to interact directly with CusF [2527]. Studies on CusB knockout (ΔCusB) and CusBΔNT have revealed a Cu(I)-sensitive phenotype in cells and indicated that M64 and M66 of CusB_NT are important residues, both for Cu(I) coordination to CusB_NT as well as for its interaction with CusF, whereas M49 of CusB_NT is important for interacting with CusF [21, 2628].…”
Section: Introductionmentioning
confidence: 99%